PEDAGOGICAL BASIS OF FORMING SCIENCE-RELATED COMPETENCES IN STUDENTS BASED ON CREATIVE-INTEGRATIVE APPROACH (Academia Science Repository, 2023)
The article talks about the development of science-related competencies in students based on a creative-integrative approach. Modern technologies and pedagogical resources used in this are analyzed. In pedagogy, the goals and tasks of developing competences related to science are studied.